Optimized Nanostructured TiO2 Photocatalysts - Topcu, Selda; Jodhani, Gagan; Gouma, Perena (Frontiers in Materials, 2016)
Titania is the most widely studied photocatalyst. In it’s mixed-phase configuration (anatase-rutile form) -as manifested in the commercially available P25 Degussa material- titania was previously found to exhibit the best photocatalytic properties reported for the pure system. A great deal of published research by various workers in the field have not fully explained the underlying mechanism for the observed behavior of mixed-phase titania photocatalysts. One of the prevalent hypothesis in the literature that is tested in this work involves the presence of small, active clusters of interwoven anatase and rutile crystallites or “catalytic “hot-spots””. Therefore, non-woven nanofibrous mats of titania were produced and upon calcination the mats consisted of nanostructured fibers with different anatase-rutile ratios. By assessing the photocatalytic and photoelectrochemical properties of these samples the optimized photocatalyst was determined. This consisted of TiO2 nanostructures annealed at 500˚C with an anatase /rutile content of 90/10. Since the performance of this material exceeded that of P25 complete structural characterization was employed to understand the catalytic mechanism involved. It was determined that the dominant factors controlling the photocatalytic behavior of the titania system are the relative particle size of the different phases of titania and the growth of rutile laths on anatase grains which allow for rapid electron transfer between the two phases. This explains how to optimize the response of the pure system.